2006
DOI: 10.1186/1476-4598-5-7
|View full text |Cite
|
Sign up to set email alerts
|

The cyclin D1 proto-oncogene is sequestered in the cytoplasm of mammalian cancer cell lines

Abstract: Background: The cyclin D1 proto-oncogene is an important regulator of G1 to S-phase transition and an important cofactor for several transcription factors in numerous cell types. Studies on neonatal cardiomyocytes and postmitotic neurons indicate that the activity of cyclin D1 may be regulated through its cytoplasmic sequestration. We have demonstrated previously, that TSA induces the ubiquitin-dependent degradation of cyclin D1 in MCF-7 breast cancer cells. Additional studies were initiated in order to furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 23 publications
(38 reference statements)
1
31
0
1
Order By: Relevance
“…At the end point, the average volume of the tumors expressing WWOX and of the control plasmid were 390 § 115 and 890 § 170 mm 3 , respectively (p < 0.001, two-way ANOVA). In addition, the average volume of the WWOX-silenced tumors was 1190 § 240 mm 3 , which was slightly bigger than the control group (890 § 170 mm 3 ). Taken together, WWOX suppressed cell proliferation in vitro and tumor growth in vivo, suggesting that WWOX acts as a tumor suppressor in prostate cancer.…”
Section: Wwox Repressed Prostate Tumor Progression In Vivo and In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…At the end point, the average volume of the tumors expressing WWOX and of the control plasmid were 390 § 115 and 890 § 170 mm 3 , respectively (p < 0.001, two-way ANOVA). In addition, the average volume of the WWOX-silenced tumors was 1190 § 240 mm 3 , which was slightly bigger than the control group (890 § 170 mm 3 ). Taken together, WWOX suppressed cell proliferation in vitro and tumor growth in vivo, suggesting that WWOX acts as a tumor suppressor in prostate cancer.…”
Section: Wwox Repressed Prostate Tumor Progression In Vivo and In Vitromentioning
confidence: 99%
“…2 The cyclin D1 proto-oncogene is an important regulator of G1 to S phase transition, and its overexpression is commonly found in cancers including prostate cancer. 3 Dysregulation of cyclin D1 has been reported to contribute to an increase not only in tumor cell growth but also in chromosome instability. 4 These alterations may further contribute to tumor progression and the acquisition of an aggressive phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…mAChR subtypes are widely expressed in the central and peripheral nervous systems [4,28]. Previous different studies postulated that muscarinic acetylcholine receptors are functional in some hematopoietic cells [8,[21][22][23][24][25][26][27][28][29]. Our previous RT-PCR studies have shown that M 2 , M 3 and M 4 mAChR subtypes are expressed in K562 cells and suggested that they are involved in regulation of NO signaling and adenylate cyclase activity [8,29].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies showed that cyclin D 1 is a predominantly cytoplasmic protein in mammalian cancer cell lines [23]. The aim of this study was to examine muscarinic receptor mediated c-Fos and cyclin D 1 gene expression in K562 cells and to investigate the intracellular signaling pathways that couple receptor stimulation to these genes.…”
Section: +mentioning
confidence: 99%
“…Besides gene amplification, cytoplasmic sequestration may also serve to regulate cyclin D1 activity in mammalian cancer cells [26]. Emerging evidence indicates that cyclin D1 may act, in part, through pathways which do not involve its role as a cell cycle regulator.…”
Section: Cyclin D and Cancermentioning
confidence: 99%